THE AQAD PRONOUNCEMENT IN SELLING AND BUYING ONLINE MUAMALAH: FUQAHA'S POINT OF VIEW - Wahairi Mahmud,; Salimah Yahaya,; Nor Adila Mohd Noor, (Journal of Islamic, Social, Economics and Development, 2022)
Recently, online business applications (e-commerce) have emerged as a novel and highly efficient means of realizing the desires of sellers and customers, particularly as the international community faces the threat of the covid-19 pandemic, which restricts their mobility. as well as socialize Independent online vendors transact without regard for space or time constraints, making it simple for purchasers. However, the contract wording, which is the basis for the legitimacy of the sales contract in the e-commerce application, must conform with Syarak. Thus, the purpose of this writing in the style of this descriptive qualitative study gives jurists' perspectives and opinions, particularly on the determination of contract wording in e-commerce applications. According to the study's findings, the practice of buying and selling online occurs without the use of a formal contract. This procedure is mandated by Islam under the condition of adhering to Sharia. This application also satisfies the parameters and pillars that Islam considers to be the foundation of the muamalah procedure. Among the fundamentals are that the goods sold may be viewed, their attributes are described, and the agreed-upon pricing terms. In order to gather information, a theoretical framework is developed by conducting a qualitative literature review. In the literature review, references to academic books and Fiqh books, articles, website information, and other materials or documentation are employed. Finally, the findings of this writing revealed that there is a view that does not allow at all the view that gives the broadest possible truth, so it is necessary to accept the third view, which is the view of Jumhur Fuqaha, Hanafi, Maliki, and Hanbali who believe that this sale and purchase transaction must be done absolutely. It is intended that this text can be utilized as a reference in purchasing and selling matters, so enhancing Malaysia's development.